The Berlin letters - Reay, Katherine, 1970- ([Nashville] : Harper Muse, 2024)
"Near the end of the Cold War, a CIA code breaker discovers a symbol she recognizes from her childhood, which launches her across the world to the heart of Berlin just before the wall comes tumbling down"--
"Includes discussion questions"--Page 4 of cover.
Keywords: Cold War -- Fiction; Berlin (Germany) -- Fiction; Thrillers (Fiction); Spy fiction; Historical fiction; Novels